Chroicocephalus ridibundus - Cibois, Alice; Vallotton, Laurent; Othman, Nagwa; Weber, Claude; Ruedi, Manuel (Zenodo, 2016)
Larus ridibundus minor , Fatio 1904 (junior homonym of Larus ridibundus minor Schlegel, 1844). 1904 Faune des vertébrés de la Suisse , p. 1507. Now Chroicocephalus ridibundus (Linnaeus, 1766). See Dickinson & Remsen, 2013: 226. Syntypes: MHNG 705.047, adult male, collected in Switzerland (Geneva) in 1844 by G. Fatio; MHNG 813.029, unsexed adult, collected in Switzerland (Geneva, unknown date) by L. Roget. Comment: Fatio’s name, being established in combination with the same generic name as Schlegel’s, is a junior objective homonym and an invalid name (Art. 53.3 of the Code). Published as part of Cibois, Alice, Vallotton, Laurent, Othman, Nagwa, Weber, Claude & Ruedi, Manuel, 2016, Type specimens of birds in the collections of the Natural History Museum of Geneva, pp. 269-282 in Revue suisse de Zoologie 123 (2) on page 271, DOI: 10.5281/zenodo.155300